Long term cyclic heat stress influences physiological responses and blood characteristics in indigenous sheep (Bangladesh Journal of Animal Science, 2013)
The present study was designed to elucidate changes in physiological and blood parameters of indigenous sheep during cyclic heat exposure. Twelve 2-4 year-old sheep with an average body weight of 10.5±0.5 kg were randomly allocated to one of three experimental heat treatments: control (21°C, stall feeding), short term (21°C to 32°C; 32°C for 4 h/d, grazing), and long term (21°C to 32°; 32°C for 8 h/d, grazing).The results have shown that sheep exposed to cyclic heat treatments exhibited higher (P=0.05) rectal temperature, body temperature, and respiratory rate compared to the control group. Cyclic heat treatments significantly decreased heart rate of sheep. There was a sharp reduction in rumination and an increase in time spent by sheep in eating during cyclic heat treatments. Long term heat treatment significantly increased RBC and WBC counts, PCV values, and hemoglobin level than that of the control and short term heat treatments. Similar responses were also observed in plasma glucose, uric acid, aspartate aminotransferase, and blood urea nitrogen levels. These results suggest that short term heat stress is tolerable but long term is physiologically detrimental to them to indigenous sheep.DOI: http://dx.doi.org/10.3329/bjas.v42i2.18486 Bang. J. Anim. Sci. 2013. 42 (2): 96-100